A new type of swaddling clothing improved development of preterm infants in neonatal intensive care units. (September 2017) - Kitase, Yuma; Sato, Yoshiaki; Takahashi, Hirokazu; Shimizu, Misaki; Ishikawa, Chie; Yamamoto, Hikaru; Hayakawa, Masahiro
Abstract: Background: Preterm infants undergo stress owing to essential treatments and exposure to the extrauterine environment in neonatal intensive care units. Aims: The aim of this study was to enable preterm infants to maintain adequate positioning with a newly developed swaddling clothing, in order to improve low muscle tone and sleep quality, and to confirm the safety of the clothing. Study design: This prospective clinical trial included an intervention group (preterm infants wearing bag-shaped clothing, allowing only exposure of the head, n = 27), and a control group (preterm infants managed only with conventional swaddling, n = 12). Outcome measures: We used the Dubowitz method to analyze behavior, recorded the frequency of vomiting and apnea in both groups, and assessed the sleep state in the intervention group. Results: Muscle tone and total score for the Dubowitz method significantly improved in the intervention group, compared with those in the control group. We evaluated the sleep state before and after the introduction of the device in the intervention group, and State 1 increased from 53.5% to 69.2% after introduction. No significant difference was seen in the frequency of vomiting and apnea between the groups. Conclusions: The new swaddling clothing with enhanced stretch capacity improved the muscle tone and increased sleep time by decreasing the state level of preterm infants. This is an effective tool to assist in infant development in neonatal intensive care units. Highlights: We have developed a new swaddling clothing for preterm infants. The new swaddling clothing might improved the muscle tone and decreased the state level. This is an effective tool to assist in development in neonatal intensive care units.